Comparative Study On The Sintering Of Calcium Phosphate Ceramic By Conventional And Microwave Sintering - Mangkonsu, Chuthathip (2014)
Sintering of calcium phosphate bioceramic were performed using microwave and conventional furnaces. The calcium phosphate precursor was used as raw material powder. Sintering of biphasic calcium phosphate (B'Cl") was successful using both sintering methods. The precursor powder was characterized by XRO, TG/ ose and particle size analysis. Sintering was done at different temperatures (1200 oe, 1250 oe, 1300 oe, 1350 oe, and 1400 Oe) using conventional and microwave furnaces. For the microwave sintering, the firing process was stopped, when the temperature reached at 1350 oe because the specimens cracked and the surfaces were damaged especially on the edge of specimens. Then the Bep specimens were characterized by XRO and FESEM while physical properties measured include density, porosity and linear shrinkage. The mechanical properties of bulk Bep were determined by using Micro Vickers hardness and diametrai tensile strength (OTS). The comparison on properties was carried out on specimens sintered at the same temperature using both methods. The XRO results showed that the f3-TCf' to (l-TCf' transformation phase occurs above 1250 oe in both sintering furnaces.